The Influence of Customer Relationship Management and Relationship Quality on Customer Life Time Value in the Insurance Industry in Malaysia - Lim Kai, Hoe (2018)
Most of the previous research studies on the effect of Customer Relationship Management, Relationship Quality and Customer Lifetime Value are in parts, but they do not holistically explore the inter-relationship between these variables and how such relationships impact on new Customer Acquisition and Retention of existing customers. This study focuses on assessing these relationships by taking a different approach that emphasizes more of the customer perspective rather than the usual company perspective. It assesses the relationship effect of Customer Relationship Management (CRM), Relationship Quality (RQ), Customer Lifetime Value (CLV) and Customer Acquisition and Retention in the insurance industry. For the purpose of investigating the interaction magnitude among the constructs, Structural Equation Modelling (SEM) has been adopted. A total of 332 valid questionnaires have been used to analyse the relationship and 4 key outcomes were produced. The result from this study has shown that Customer Relationship Management has a direct positive effect on the Relationship Quality as well as Customer Lifetime Value (CLV). Also, it was established that the Relationship Quality (RQ) has a direct positive influence on Customer Lifetime Value (CLV) in terms of usage quantity, loyalty, word-of-mouth and purchase intention. Lastly, the study also confirmed that the inter-relationships between Customer Relationship Management (CRM), Relationship Quality (RQ) and Customer Lifetime Value (CLV) have positively affected new customer acquisition and retention of existing customer, but with a mixed outcome especially for Customer Lifetime Value. However, the results showed that only Purchase Intention and Word-of-Mouth have shown significant relationship on new customer acquisition and retention of the existing customer. Loyalty and Usage Quantity, on the other hand, iii only showed a positive relationship but they do not affect new customer acquisition and retention of existing customer. Overall, the findings of the study suggest that, given the limited resources of the insurance company, it should focus on the right factors to enhance customer experience and perception that will translate into better profit for the company. Furthermore, factors such as Customer Relationship Management, Relationship Quality and Customer Lifetime Value should be reviewed as parts of a holistic relationship to generate the desired result of attracting (acquiring) new customers and retaining existing customers, with the outcome of sustaining or improving company profit.